(untitled) (Salam International Academic Journal, 2020)
The Holy Qur’an is the word of God (Allah), and the eventual message of ‎Allah revealed for the guidance of mankind, so therefor, this book is the ‎ultimate guide for Muslims in their life. As Allah indicates it in Quran ‎through the following verse ‎‏(هَـذَا بَيَانٌ لِّلنَّاسِ وَهُدًى وَمَوْعِظَةٌ لِّلْمُتَّقِينَ) ‏ Interpretation: This is the caveat or warning for people; guidance for ‎those who fear from Allah.‎ Muslims throughout the history so far have served this great book in ‎every way, and if God willing, it will continue till the Day of Judgment. ‎The great scholars of Ummah have devoted their life to the service of the ‎Holy Qur’an; they have done unparalleled services in the field. In the ‎process of these services rendered by great scholars one of them is, the ‎exegesis or interpretation of the Holy Qur’an carried out by hundreds of ‎great scholars and based on their abilities and skills they have presented ‎the Quranic perceptions to mankind. ‎ Praise be to Allaah. Now we have hundreds of printed and unprinted ‎interpretations and exegesis in the Islamic Library; each with its own ‎precious gems.‎ Generally, the interpretation or exegesis of Holly Quran is categorized ‎into four types such as (analytical, concise, comparative and thematic).‎ In the field of exegesis (Tafseer), the study and thematic interpretation ‎is relatively new, so therefor, in this article we have tried to explore the ‎essential and fundamental aspects of thematic interpretation and ‎present it to our respected readers particularly to those readers who are ‎really interested in Quranic education. In this article, following points ‎are taken into account based on the article.‎ v ‎ Introduction of thematic interpretation (Tafseer)‎ v Historical stages of thematic interpretation (Tafseer)‎ v Reasons for the emergence of thematic interpretation (Tafseer)‎ v Types of thematic interpretation (Tafseer)‎ v Difference in procedure between thematic interpretation and other ‎interpretations (Tafseer) ‎ v Benefits of thematic interpretation v Special books and articles regarding thematic interpretation